Chronobiotic and cytoprotective activity of melatonin in the cardiovascular system. Doses matter - Cardinali, Daniel Pedro (2024)
A circadian disruption, manifested by disturbed sleep and low-grade inflammation, is commonly seen in cardiovascular diseases (CVDs). The decline in plasma melatonin, which is a conservedphylogenetic molecule across all known aerobic creatures, is also a common feature in CVDs. Thedaily evening pineal melatonin surge synchronizes both the central pacemaker located in thehypothalamic suprachiasmatic nuclei and myriads of cellular clocks in the periphery (“chronobioticeffect”). Melatonin also has cytoprotective properties, acting primarily not only as an antioxidant bybuffering free radicals but also by regulating inflammation. In CVDs, exogenous melatoninadministration decreases nocturnal hypertension, improves systolic and diastolic blood pressure,reduces the pulsatility index in the internal carotid artery, decreases platelet aggregation, and reduces serum catecholamine levels. Melatonin evokes an increase in parasympathetic activity in the heart. Allometric calculations based on animal research show that melatonin’s cytoprotective benefits in CVDs may require high doses to be fully manifested (in the 100–200 mg/day range). If melatonin is expected to improve health in CVDs, the low doses currently used in clinical trials (i.e., 2–10 mg) are presumably insufficient.